A comparative study of Laryngeal Mask Airway size 1 vs i‐gel size 1 in infants undergoing daycare procedures. Issue 4 (11th October 2014) - Pant, Deepanjali; Koul, Archna; Sharma, Bimla; Sood, Jayashree; Lerman, Jerrold
Summary Background The i‐gel size 1 is a relatively new, single use, second generation supraglottic airway device. This prospective, randomized, observational study compares the suitability of the i‐gel size 1 with the classical Laryngeal Mask Airway (cLaryngeal Mask Airway) size 1 in pediatric patients undergoing elective daycare procedures. Methods Forty ASA I and II children (2–5 kg body weight) were randomized to two groups of 20 each, to receive either the i‐gel or the cLaryngeal Mask Airway as an airway device. The primary outcome variable was oropharyngeal seal pressure (OSP). We also assessed ease of insertion, number of insertion attempts, time taken for successful insertion and any intra‐operative complications. Results Demographic data did not differ between the two groups. The OSP with the i‐gel was 22.30 ± 4.72 cm H2O as compared to 18.05 ± 1.95 cm H2O with the cLaryngeal Mask Airway and the difference was statistically significant (P = 0.001). Displacement of the airway device following change of position was reported less often with the i‐gel as compared to the cLaryngeal Mask Airway [n = 1 (5%) vs n = 5 (35%), P = 0.04]. There were no major complications with either device and rest of all the variables were comparable with both the devices. Conclusions The OSP of the i‐gel size 1 was higher than that of the cLaryngeal Mask Airway. This was statistically significant, although may not be of clinical significance. The i‐gel size 1 is less prone to displacement during position changes. However, being a preliminary study carried out on a small number of patients, further trials are warranted to come to any definite conclusion.